The influence of the relationship between emotional intelligence and leadership on the job satisfaction of educators in Free State schools - Oosthuyse, Barend Gabriel (University of the Free State, 2009)
Since the publication of Goleman’s book ‘Emotional Intelligence’ in 1995, the interest and research into EI has experienced a phenomenal growth, particularly in the commercial sector. Research by Goleman, Boyatzis and McKee, Bar-On, Cooper and Sawaf, as well as many other researchers, indicates that EI is fundamental to successful leadership as it enhances intra- and interpersonal competencies that influence job satisfaction. This implies that EI may play a major role in retaining educators since research by the HSRC found a high level of dissatisfaction and an intention to leave the profession amongst educators in South Africa. The EI domain of self-awareness allows leaders to accept themselves, thereby affording them the self-confidence to accept others for who they are. Self-awareness enables leaders to create a realistic and inspiring vision by enlisting the cooperation of others through the assertive and convincing communication of a positive vision when they believe in themselves and without being egotistic. EI furthermore allows leaders to become aware of the emotions and needs of others, which is very important to job satisfaction as positive attitudes are created through the fulfilment of these needs. This EI domain of social awareness is thus crucial to becoming considerate of others’ preferences, their needs of affiliation, their achievement and recognition and their abilities and expectations. These may then be utilised in successful shared decision making and delegation so as to allow personal and professional growth, which may enhance the self-actualisation of educators. EI additionally affords leaders the ability to understand emotions, as well as to manage their own and others’ emotions. These EI domains allow leaders to create and sustain positive attitudes, motivate, encourage, empathetically support and trust educators to act autonomously and responsibly to achieve the success and growth required to enhance their self-esteem. Furthermore, EI assists leaders to accept diversity, be flexible and adaptable, to involve and consult educators in participative leadership and empower educators through delegation that inspires them to actualise their full potential by experiencing achievement, comfort, safety, autonomy and status. Moreover, it enables leaders to handle conflict, frustration and stress in ways that allow them to stand out as models to emulate. The complexity of leadership, particularly in education where the vested authority is at odds with education leaders, who should be educator-centred, and the Department of Education as a bureaucratic managerialistic system, complicates the study and the achievement of job satisfaction in the South African educational milieu. The quantitative and qualitative data analysis revealed that although education leaders exhibit deficiencies, the majority of leaders are proficient in EI and leadership practices that allow educators to experience job satisfaction. The largest sources of dissatisfaction were identified to be a lack of educator compensation in relation to work done; little chance for advancement; being responsible for too many extra-curricula activities; and an overload of bureaucratic red-tape caused by departmental policies and practices mainly stemming from the Department of Education. Other sources of dissatisfaction which are the responsibility of education leaders were identified. These included ability utilisation and recognition which affected, in particular, the older, more experienced and better qualified educators. Recommendations regarding areas that should be addressed were made. These recommendations include the scientific evaluation of education leaders to determine their EI and leadership abilities so as to appoint the most suitable leaders to enhance effective education and educator job satisfaction. Existing leaders should also be evaluated to address specific incapacitating deficiencies as EI may be learned through selective training, which includes active learning and the application of newly learned competencies. Emotionally intelligent education leaders seem to possess the leadership qualities that enable them to enhance the lives of educators through their caring servant leadership, making possible personal growth towards an improvement in job satisfaction. This satisfaction is fundamental to successful education since only contented and passionate educators will produce positive results and achieve excellence in their respective schools.

Sedert die verskyning van Goleman se boek Emotional Intelligence in 1995, het die belangstelling en navorsing in EI fenomenale groei beleef, veral in die handelswêreld. Navorsing deur Goleman, Boyatzis en McKee, Bar-on, Cooper en Sawaf, asook verskeie ander navorsers, het aangedui dat EI grondliggend is aan suksesvolle leierskap, omdat dit intra- en interpersoonlike vaardighede verhoog, wat werksbevrediging beïnvloed. Dit impliseer dat EI ‘n belangrike rol in die behoud van opvoeders kan vertolk, aangesien navorsing deur die RGN bevind het dat daar hoë vlakke van ontevredenheid, asook die voorneme om die professie te verlaat, by opvoeders in Suid-Afrika is. Die EI-domein van selfbewussyn stel leiers in staat om hulself te aanvaar, waardeur hulle die selfvertroue verkry om ander te aanvaar soos hulle is. Leiers het selfvertroue, soos deur laasgenoemde gevestig, nodig. Selfbewussyn stel leiers in staat om ’n realistiese en inspirerende visie te skep deur die samewerking van ander te verkry. Hulle kommunikeer met selfversekerdheid en oortuiging ’n positiewe visie, sonder om egoïsties te wees. Daarby stel EI leiers in staat om bewus te wees van die emosies en behoeftes van ander. Dit is baie belangrik vir werksbevrediging, aangesien positiewe houdings geskep word deur die vervulling van daardie behoeftes. Hierdie EI-domein van sosiale bewussyn is dus noodsaaklik vir bedagsaamheid teenoor ander se voorkeure, behoeftes aan affiliasie, prestasie en erkenning, vermoëns en verwagtinge. Laasgenoemde kan dan aangewend word in suksesvolle gesamentlike besluitneming en delegering, wat persoonlike en professionele groei meebring en die selfverwesenliking van opvoeders verhoog. Daarby gee EI leiers die vermoë om emosies te verstaan en te gebruik, asook om hul eie en ander se emosies te bestuur. Hierdie EI-domeine stel leiers in staat om positiewe houdings te skep en onderhou, opvoeders te motiveer, aan te moedig, empaties te ondersteun en te vertrou om outonoom en verantwoordelik op te tree, sodat hulle sukses en groei kan behaal wat hul gevoel van eiewaarde sal verhoog. Boonop stel dit leiers in staat om verskeidenheid te aanvaar, buigsaam en aanpasbaar genoeg te wees om opvoeders te betrek en te raadpleeg in deelnemende bestuur. Delegering bemagtig opvoeders en inspireer hulle om hul volle potensiaal te verwesenlik deur prestasie, gemak, veiligheid, outonomie en status te beleef. Verder is dit vir leiers moontlik om konflik, frustrasie en spanning te hanteer op so ’n wyse dat dit hulle laat uitstaan as voorbeelde om na te volg. Die kompleksiteit van leierskap, veral in onderwys waar die gesag berus by die onderwysleiers, wat opvoeder-gesentreerd behoort te wees, en die Departement van Onderwys as die burokratiese bestuurstelsel, bemoeilik die studie en verkryging van werksbevrediging in die Suid-Afrikaanse onderwysmilieu. Die kwantitatiewe en kwalitatiewe ontleding van data het aan die lig gebring dat, alhoewel onderwysleiers tekortkominge vertoon, die meeste leiers bedrewe is ten opsigte van EI, asook leierskapuitvoering wat opvoeders in staat stel om werksbevrediging te beleef. Vergoeding vir opvoeders in verhouding tot die werk wat gedoen word, die uiters skraal kans vir bevordering en ’n werksoorlading, veroorsaak deur departementele beleid en –praktyke en dus die Departement van Onderwys se verantwoordelikheid, is geïdentifiseer as die belangrikste bronne van ontevredenheid. Ander bronne van ontevredenheid, wat meer die verantwoordelikheid van onderwysleiers is, is ook geïdentifiseer. Dit het aanwending van kundigheid asook erkenning ingesluit. Dit het veral ouer, meer ervare en beter gekwalifiseerde opvoeders geraak. Aanbevelings is gemaak rakende areas wat behoort aangespreek te word. Hierdie aanbevelings sluit die wetenskaplike evaluering van onderwysleiers, om hulle EI en leierskapvermoëns vas te stel, in. Dit sal meebring dat die mees geskikte leiers, wat effektiewe onderwys en werksbevrediging vir onderwysers sal bevorder, aangestel kan word. Bestaande leiers behoort ook geëvalueer te word om spesifieke remmende tekortkominge aan te spreek, aangesien EI aangeleer kan word deur selektiewe opleiding, wat aktiewe leer en die aanwending van nuut aangeleerde vaardighede insluit. Emosioneel-intelligente onderwysleiers skyn die leierseienskappe te besit wat hulle in staat stel om die lewens van opvoeders te verbeter deurdat hulle simpatieke dienskneg-leierskap persoonlike groei toelaat, wat op sy beurt verbeterde werksbevrediging meebring. Hierdie bevrediging is grondliggend aan suksesvolle onderwys, aangesien slegs gelukkige, geesdriftige opvoeders positiewe uitslae en uitnemendheid behaal.
Thesis (Ph.D. (Comparative Education and Education Management))--University of the Free State, 2009
Keywords: Emotion; Intelligence; Leadership; Education; Job satisfaction; Teachers -- Job satisfaction; Emotional intelligence; Educational psychology; Educational leadership -- South Africa